Code-switching as a translatorial practice within the Italian national minority in Slovenia - Umer Kljun, Jerneja (Stridon, 2024)
The paper explores the occurrence of code-switching as a form of translatoriality among members of the Italian national minority in Slovenia. As a continuation of a wider sociolinguistic study, which brought a comprehensive analysis of 1,389 instanc-es of code switching between Italian and Slovene among bilingual speakers, the paper examines the intersection between code switching and self-translatoriality by study-ing 85 instances of bilingual reiteration in spontaneous and semi-spontaneous speech. By observing these instances from the perspective of translatoriality, the paper pre-sents a case study on the translatorial actions that occur in such bilingual utterances, i.e. summarizing, duplicating, expanding and complementary language practices, as well as their underlying motivation and purpose, while also highlighting the practice of intercomprehension among bilingual speakers within the culturally and linguisti-cally diverse community of the Slovene coast. The data show that self-translatoriality occurs both in in-group and out-group bilingual communication, although more fre-quently in the context of public events aimed at the broader multilingual community. While duplicating language practices occur in all settings, speakers often only repeat the nearest element, which leads to a fragmentation of the message. Translatorial ac-tion types are also frequently combined, producing fluid bilingual utterances that pre-suppose a plurilingual competence among all participants.
Keywords: code-switching; intercomprehension; jezikovna manjšina; kodno preklapljanje; linguistic minority; medjezikovno razumevanje; prevajalskost; samoprevajalskost; self-translatoriality; translatoriality